Inequality of educational opportunities: Evidence from Brazil - Marcos Vinicio Wink Junior; Luis Henrique Zanandréa Paese (EconomiA, 2019)
This paper aims to estimate the inequalities of educational opportunities of 5th and 9th-grade students in Brazil and its states, verifying the relative contribution of each analyzed variable to this inequality. For this purpose, we used the new methodology developed by Ferreira and Gignoux (2014) considering the data of standardized tests of proficiency in Portuguese Language and Mathematics. Overall, the results show that more than 15% of the inequality of educational opportunities in Brazil is explained by circumstances unrelated to individual effort. The poorest regions of Brazil are also those with the highest inequality of educational opportunities and the circumstances with the greatest power to explain inequalities being parental education and socioeconomic status.
Keywords: D63; I24; O12; 330; Educational achievement; Inequality of opportunity; Brazil